The effect of gamma irradiation on the germination and growth of Turda Star maize hybrid dry samples - Marcu, Delia; Cosma, Constantin (Acta Agraria Debreceniensis, 2010)
In order to study the effects of gamma rays on germination indices i.e. germination index (GI), total germination (GT) and the germination energy (GE), of maize hybrid, Turda Star current experiment was conducted. Dry seeds of Turda Star maize hybrid were irradiated with 2, 5, 15, 30 and 50 Gy, using a 60Co-gamma radiation source. Results showed that gamma irradiation affected all the above mentioned parameters except germination percentage. Total germination and germination energy was significantly affected at higher doses of gamma rays. However, increasing doses of gamma rays did not have significant effects on seed germination percentage. The other growth parameters showed declining tendency with increasing doses of gamma irradiation.